Long-term impact of bariatric surgery in diabetic nephropathy - Young, LeAnne; Nor Hanipah, Zubaidah; Brethauer, Stacy A.; Schauer, Philip R.; Aminian, Ali (Springer, 2019)
Background: Bariatric surgery has been shown to improve and resolve diabetes. However, limited literature about its impact on end-organ complications of diabetes is available. The aim of this study was to examine the long-term effect of bariatric surgery on albuminuria.